Inculcating tsunami awareness in a mathematics lesson: improving students' collaborative problem solving via lesson study - Khalid, Madihah; Pg. Hj Ali, Dk Haslinah (Southeast Asian Ministers of Education Organization (SEAMEO), 2016)
The past two cycles of PISA have reflected the demands of the skills and competencies that many countries desire their future generations to possess. Among these competencies, students’ financial literacy, problem solving, and communication skills have emerged to be as important as their reading and quantitative literacy (OECD, 2013). Problem-solving, along with other 21st century skills can be inculcated in the students by using the problem-solving pedagogy. However, teachers who are not used to teaching mathematics via problem solving need to experience the pedagogy themselves and this can be best achieved by implementing Lesson Study. A Lesson Study research study was conducted to look at collaborative problem solving in the teaching of the topic on “rate” to year 5 students. Results showed that students benefited from their lesson in terms of increased knowledge of the problem context and the ability to apply knowledge of rates in finding the best solution that the problem posed. Consequently, Lesson Study was found to help enhance teachers’ pedagogical content knowledge. It helped them produce effective lesson plans that incorporated student-centred authentic lessons that also integrated values, use of technology and students’ creativity in problem solving.